(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The idea of perceived organizational performance, which may be believed to be a reflection of the actual performance, is also crucial in terms of employee attitudes, and previous research has linked a favorableorganizational environment to increased levels of organizational commitment. Due to the nature of the service provided, these factors are particularly relevant in healthcare settings. Thus, the employees’ mental frames might affect the quality of service they provide. The purpose of this study was to determine the organizational environment’s impact on organizational commitment and perceived organizational performance from the viewpoint of healthcare employees. This quantitative study used a self-administered questionnaire to gather information from healthcare professionals working in Indian public hospitals. Linear regression analyses were utilized to make sense of the data we gathered. Both employee dedication and satisfaction with the company’s success were shown to be significantly connected with the atmosphere at their workplace. The results of a simple linear regression analysis showed that an optimistic work environment significantly predicts employee loyalty and positive evaluations of the company’s success. We found a linear and positively correlated link between organizational atmosphere, employee dedication, and evaluations of the organization’s effectiveness.